Biofortified Calcium Phosphate Nanoparticles Elicit Secondary Metabolite Production in Carob Callus via Biosynthetic Pathway Activation - Doaa E. Elsherif; Fatmah A. Safhi; Mai A. El-Esawy; Alaa T. Mohammed; Osama A. Alaziz; Prasanta K. Subudhi; Abdelghany S. Shaban (Plants)
Plant callus cultures are a sustainable alternative for producing bioactive secondary metabolites, but their low yields limit industrial applications. Carob (Ceratonia siliqua L.) is rich in medicinally valuable compounds, yet conventional cultivation faces challenges. To address this, we use biofortified calcium phosphate nanoparticles, which refer to CaP-NPs that have been enriched with bioactive compounds via green synthesis using Jania rubens extract, thereby enhancing their functional properties as elicitors in carob callus. CaP-NPs were green-synthesized using Jania rubens extract and applied to 7-week-old callus cultures at 0, 25, 50, and 75 mg/L concentrations. At the optimal concentration (50 mg/L), CaP-NPs increased callus fresh weight by 23.9% and dry weight by 35.1%. At 50 mg/L CaP-NPs, phenolic content increased by 95.7%, flavonoids by 34.4%, tannins by 131.8%, and terpenoids by 211.9% compared to controls. Total antioxidant capacity rose by 76.2%, while oxidative stress markers malondialdehyde (MDA) and hydrogen peroxide (H2O2) decreased by 34.8% and 14.1%, respectively. Gene expression analysis revealed upregulation of PAL (4-fold), CHI (3.15-fold), FLS (1.16-fold), MVK (8.3-fold), and TA (3.24-fold) at 50 mg/L CaP-NPs. Higher doses (75 mg/L) induced oxidative damage, demonstrating a hormetic threshold. These findings indicate that CaP-NPs effectively enhance secondary metabolite production in carob callus by modulating biosynthetic pathways and redox balance, offering a scalable, eco-friendly approach for pharmaceutical and nutraceutical applications.